+0  
 
0
74
2
avatar+2206 

#11 Help.

NotSoSmart  Feb 6, 2018

Best Answer 

 #2
avatar+6943 
+2

(f o g)(4)   =   f( g(4) )

 

g(x)   =   -2x - 6

g(4)   =   -2(4) - 6

g(4)   =   -8 - 6

g(4)   =   -14

 

(f o g)(4)   =   f( g(4) )   =   f( -14 )

 

f(x)   =   3x - 7

f( -14 )   =   3(-14) - 7

f( -14 )   =   -42 - 7

f( -14 )   =   -49

 

(f o g)(4)   =   f( g(4) )   =   f( -14 )   =   -49

hectictar  Feb 6, 2018
Sort: 

2+0 Answers

 #1
avatar+588 
0

Is "find (f * g)(4)" meant to be written in that way, or is it suppose to be (f * g)(x)?

adore.nuk  Feb 6, 2018
 #2
avatar+6943 
+2
Best Answer

(f o g)(4)   =   f( g(4) )

 

g(x)   =   -2x - 6

g(4)   =   -2(4) - 6

g(4)   =   -8 - 6

g(4)   =   -14

 

(f o g)(4)   =   f( g(4) )   =   f( -14 )

 

f(x)   =   3x - 7

f( -14 )   =   3(-14) - 7

f( -14 )   =   -42 - 7

f( -14 )   =   -49

 

(f o g)(4)   =   f( g(4) )   =   f( -14 )   =   -49

hectictar  Feb 6, 2018

22 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details